Mediterranean diet and adiposity in children and adolescents: A systematic review. (23rd November 2021) - Lassale, Camille; Fitó, Montserrat; Morales‐Suárez‐Varela, María; Moya, Andrés; Gómez, Santiago F.; Schröder, Helmut
Summary: Our aim was to summarize, through a systematic review, the current evidence from dietary intervention and observational studies on the impact of adherence to the Mediterranean diet on adiposity markers and obesity in children and adolescents. We searched Medline up to June 1, 2021 for the identification of intervention and observational studies meeting the inclusion criteria, following the PRISMA statement. We included 55 articles: 8 intervention studies and 47 observational studies. Three trials report a beneficial effect of the dietary intervention, whereas two did not, and three did not compare with a control. All observational studies were cross‐sectional, and only five studies also included a longitudinal analysis. More than half of the cross‐sectional studies found no significant association between adherence to Mediterranean diet and adiposity. Three out of the five longitudinal studies found a negative association. The majority of both observational and intervention studies was of low quality. Despite a large number of published studies, overall, there is only limited evidence of a beneficial effect of following a traditional Mediterranean diet to maintain a healthy body weight in childhood. More high‐quality intervention and longitudinal data are needed to form the base of large‐scale health programs to prevent childhood obesity.